ISOLATION, CHARACTERIZATION AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF DIARRHEAGENIC ESCHERICHIA COLI (DEC) AMONG CHILDREN ATTENDING SOME SELECTED HOSPITALS WITHIN KADUNA METROPOLIS (FUDMA JOURNAL OF SCIENCES, 2022)
Diarrhoea has been associated with significant morbidity and mortality, ranked the second cause of death in children aged 0 to 5 years. Bacteria, viruses, protozoa, and helminths have all been implicated in diarrhoea, however rotavirus and diarrhoeagenic E. coli (DEC) are the most common cause. This study aimed to determine the antibiotic susceptibility pattern of diarrheagenic Escherichia coli isolated from children 0-5 years attending selected hospitals in Kaduna metropolis. A total of 264 stool samples were collected from children attending four selected hospitals in Kaduna metropolis. Standard culture procedures and molecular techniques such as PCR and 16s rRNA were employed in isolation and characterization of diarrhoeagenic E. coli from the stool samples. The study established a prevalence of 24.2% for diarrheagenic Escherichia coli, and all the isolates demonstrated multiple antimicrobial resistance index (MARI) of 0.5 and above, and showed significant resistance against augmentin (100%), amoxacillin (100%), ampicillin-cloxacillin (ampiclox) (100%), erythromycin (100%), gentamycin (100%), cefoxitin (100%), cefuroxime (95%), ceftriazone (95%) and ceftaxidime (85%). The least (60%) resistance was observed against imipenem. The study concluded that antibiotics have not been very effective in the treatment of E. coli-related diarrhoea. The study, therefore, recommends the implementation of programmes geared towards good hygiene, good nutrition and good health
Keywords: Diarrhoea, Diarrhoeagenic E.coli (DEC), Kaduna, Multidrug resistance (MDR)